Anaesthesia for laparoscopic abdominal surgery: A survey on the choice of airway management amongst anaesthesiologists / Imaan Abdul Rahim - Imaan, Abdul Rahim (2019)
Background Laparoscopic abdominal surgery is now a widely established minimally invasive surgical technique. Anaesthetic techniques have evolved and been refined to tailor to the anticipated physiological changes associated with laparoscopic abdominal surgery. The cuffed tracheal tube was previously thought to be the gold-standard airway management in laparoscopic abdominal surgeries. This is slowly being replaced by second generation supraglottic airway devices. This survey aims to examine and compare practices in airway management in laparoscopic abdominal surgery. Methods This study is a cross-sectional survey involving various government and private hospitals in the Klang Valley and Selangor. The survey questionnaire was distributed via email in Google Form format. The responses were tabulated and analysed, with the chisquare test performed to calculate p-value for sector and experience. Results The questionnaire was distributed to a total of 129 anaesthesiologists. Out of those, we received 95 responses but were only able to use 90 after considering inclusion and exclusion criteria. The majority of respondents (67.8%) use only ETT whereas 32.2% use LMA. Cross tabulation revealed significant correlation between work sector and iv duration of experience in choice of airway management with p value for each being 0.009 and 0.027 respectively. Most in the LMA group choose low risk patients and maintain certain parameters to minimise risk of aspiration. The ETT-only group mainly cited lack of experience of junior colleagues and support staff, and potential medicolegal repercussions (49.1%, 39.2% and 39.2% respectively) as reasons for their choice. Conclusion Junior trainees and anaesthetic support staff should be educated on how to ensure safe usage of LMA in laparoscopic abdominal surgery. At the same time, more evidence needs to be gathered to enable the provision of such a training. A localised protocol could also be created to ensure standard practices can be implemented in the use of LMA in LAS.